Dimensionally Engineered Perovskite Heterostructure for Photovoltaic and Optoelectronic Applications. Issue 45 (30th October 2019) - Heo, Sung; Seo, Gabseok; Cho, Kyung Taek; Lee, Yonghui; Paek, Sanghyun; Kim, Sung; Seol, Minsu; Kim, Seong Heon; Yun, Dong‐Jin; Kim, Kihong; Park, Jucheol; Lee, Jaehan; et al.
Abstract: Although 2D|3D has shown potential for application in multifunctional devices, the principle of operation for multifunction devices (SOLAR Cell‐LED: SOLED) has not yet been revealed. However, most studies have reported that the devices have only one auspicious characteristic. Here in this study the SOLED devices are monitored and investigated in a 2D|3D heterostructure with a multidimensional perovskite. It is fond that a 2D|3D heterostructure with a multidimensional perovskite interface induces carrier transmission from the interface, increasing the density of electrons and holes, and increasing their recombination. An interface‐engineered perovskite 2D|3D‐heterojunction structure is employed to realize the multifunctional photonic device in on‐chip, exhibiting overall power conversion efficiencies of photovoltaics up to 21.02% under AM1.5, and external quantum efficiency of the light‐emitting diode up to 5.13%. This novel phenomenon is attributed to carrier transfer resulting in a high carrier density and enhanced carrier recombination at the 2D|3D interface. Abstract : Here, an interface‐engineered perovskite 2D|3D‐heterojunction structure is employed to realize a multifunctional photonic device on‐chip, exhibiting power conversion efficiencies of up to 21.02% under AM1.5, and an external quantum efficiency for the light emitting diode up to 5.13%. This novel phenomenon is attributed to carrier transfer resulting in a high carrier density and enhanced carrier recombination at the 2D|3D interface.